Self-Efficacy Parents in Undergoing Child Cancer Treatment at the Rumah Kanker Anak Cinta Bandung - Sri Hendrawati; Ikeu Nurhidayah; Ai Mardhiyah (Faculty of Nursing, Universitas Jember, 2019)
The incidence of cancer in children is increasing and has entered into the top ten most prevalent diseases in children. Cancer in children have an impact both physical and psychosocial changes that can occur as a result of the disease and the side effects of treatment. The treatment for children with cancer should be done continuously and lasts a long time, so the role of parents in supporting the treatment is very important. Parents are the important factors to implementation of family centered care in the treatment and care for children with cancer. The implementation of family centered care is influenced by the self efficacy belief of parents. This study aimed to identify parental self efficacy in the treatment of children with cancer at the Rumah Kanker Anak Cinta Bandung. This study used a descriptive quantitative. The sample in this study was chosen by consecutive sampling, and found 40 samples within a month. Data collection using questionnaires developed based on Bandura theory (1997). Data was analyzed using descriptive analyzes by frequency and persentation. The results showed that the majority of parents who have children with cancer have a high self efficacy as many as 23 people (57.5%). Parents who have children with cancer in this study had a high ability or confidence (self efficacy) in treating children with cancer. So that it can be very supportive for the process of care, treatment, and cure of children, which expected to improve the quality of life for children with cancer.